Innovative Places in Europe: Research Clustering, Co-Patenting Networks and the Growth of Regions - Julian Phillip Christ (Peter Lang International Academic Publishers, 2012)
Regional disparities and spatial clustering are ubiquitous in today's world. This study contributes with empirical findings on the distribution of European research and patenting activity since the 1980s at the regional level. Besides a general theoretical part, it offers a quantitative clustering analysis, which makes use of EPO patent applications and a harmonized regional and technological classification. Moreover, the pan-European study incorporates a structural analysis of inter-regional co-patenting networks at the regional and technological level that covers the 1990s and 2000s. Finally, European regional income and growth disparities are addressed by placing emphasis on the spatial distribution of research activity and the regional settlement structure.
Keywords: 330